2019
DOI: 10.1002/tox.22843
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoke components on myocardial differentiation of mouse embryonic stem cells

Abstract: The heart is the first organ formed in the developing fetus, and abnormal development of the heart is a major cause of fetal death. The adverse effects of cigarette smoke on the heart have been well established, but it is not well understood how cigarette smoke components regulate signaling molecules and cardiac specific functions during the early differentiation stage of the embryonic heart. In this study, we identified changes in the size of mouse embryoid bodies (mEBs) in response to treatment with cigarett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…In addition, it has been reported that smoke can damage DNA, which increases the protein expression of p53. 36 Heterogeneous nuclear ribonucleoproteins (HNRNPs) are a class of RNA-binding proteins that include ~20 proteins and are divided into HNRNPAl-U, depending on the molecular weight. The RNA-binding specificity of each protein depends on the sequence of the RNA-binding region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been reported that smoke can damage DNA, which increases the protein expression of p53. 36 Heterogeneous nuclear ribonucleoproteins (HNRNPs) are a class of RNA-binding proteins that include ~20 proteins and are divided into HNRNPAl-U, depending on the molecular weight. The RNA-binding specificity of each protein depends on the sequence of the RNA-binding region.…”
Section: Discussionmentioning
confidence: 99%
“…As a cancerogen, tobacco smoke can activate a higher frequency of TP53 mutations, which may lead to craniofacial malformation. In addition, it has been reported that smoke can damage DNA, which increases the protein expression of p53 36 …”
Section: Discussionmentioning
confidence: 99%
“…In hypoxia-treated mESCs, treatment with melatonin 500 μM stabilized the cells' beating ratio. Beating ratio of stem cell-derived cardiomyocyte has been known to be sensitive to environmental stress during differentiation [ 30 ]. Our results suggest that 500 µM of melatonin treatment hold a protective effect against hypoxic stress during differentiation.…”
Section: Discussionmentioning
confidence: 99%